IMPLEMENTATION OF 360-DEGREE FEEDBACK AND SAW FOR DECISION SUPPORT SYSTEM OF ACHIEVING TEACHER'S RECOMMENDATION - Novita BR Ginting; Zulkarnaen Noor Syarif; Mamay Maesaroh; Jejen Jaenudin; Dahlia Widhyaesteoty; Muhamad Alfian Yusup; Leny Tritanto Ningrum (Kresnamedia Publisher, 2022)
Education requires quality teacher resources in the current era of industry 4.0 and society 5.0. Teachers act as educators, teachers, mentors, directors, trainers, assessors, and evaluators. Students must have critical thinking competencies, creativity and innovation, interpersonal and communication skills, teamwork and collaboration, and self-confidence. At SMK Yasbam, the selection process for outstanding teachers is carried out every year. The problem faced is that the selection process is still assessed, selected, and determined by the school principal only, so there is still a process that is deemed not transparent, accountable, and fair. To make the assessment process fairer, try using the 360-degree feedback method, a multi-source assessment, and then weighting the performance value using the Simple Additive Weighting method to obtain recommendations for outstanding teachers. Respondents consisted of principals, fellow teachers, students, and themselves (the assessed teachers). Furthermore, combining these two methods is applied in a decision support system to make the assessment process and selection of outstanding teachers more objective.